PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Syafira Khairanisa Salma (2020)
This research was conducted to examine the effect of the variable Profitability, Firm Size and Audit Committee on Sustainability Report Disclosure. The sample in this research amounted to 28 Companies that follows Sustainability Report Awards in the 2015-2018 period that were selected using pool sampling. Testing the hypothesis in this study was used Multiple Linear Regression Analisys using STATA 13 analysis tool with a significant level of 5 %. The results of this research indicate that (1) Profitability has no effect on Sustainability Report Disclosure (2) Firm size has negative effect on Sustainability Report Disclosure (3) Audit Committee has no effect on Sustainability Report Disclosure.